A vision on the 'foodture' role of dietary exposure sciences in the interplay between food safety and nutrition. (February 2022) - Jeddi, Maryam Zare; Boon, Polly E.; Cubadda, Francesco; Hoogenboom, Ron; Mol, Hans; Verhagen, Hans; Sijm, Dick T.H.M.
Abstract: Background: In this paper, the European chapter of the International Society for Exposure Science (ISES Europe) provides a vision on how dietary exposure sciences can contribute to address the challenges in the field of food safety and nutrition due to changes in food systems by answering the following question: How can we assess timely and accurately changes in dietary exposure to hazardous chemicals (and mixtures thereof) or intake of nutrients due to changes in food production, food consumption and food composition? Scope and approach: We first describe the current role of dietary exposure sciences and the instruments that are being used to assess dietary exposure in food safety and nutrition. This is followed by an analysis of current changes and developments, primarily at the European level, relevant for food safety and nutrition. This results in a list of identified challenges for dietary exposure sciences. Key findings and conclusions: We thus focus on the timely and accurate assessment of the impact of changes and developments on consumer's and public health, from the perspective of dietary exposure sciences. This includes making better use of chemical analysis, dietary exposure assessment and human biomonitoring, providing increased insight in food composition and nutrients, taking into account the impact of new technologies on human exposure, and making better use of risk-benefit assessment. Highlights: There is an urgent need to improve efficiency and effectiveness of dietary exposure assessment tools. Therefore, the potential impact of dietary exposure sciences on food safety and nutrition is reviewed. The most important changes and developments relevant for food safety and nutrition are discussed. Recent developments and trends related to food safety will impact the consumer exposure to emerging risks. Changing patterns of consumer choice and food consumption and compositions are the most important aspect of dietary exposure.